2023
DOI: 10.3389/fphar.2023.1028257
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of traditional Chinese medicine injection for diabetic kidney disease: A network meta analysis and systematic review

Abstract: Background: Diabetic kidney disease (DKD) is an important public health problem worldwide that increases the mortality of patients and incurs high medical costs. Traditional Chinese Medicine injections (TCMIs) are widely used in clinical practice. However, their efficacy is unknown owing to a lack of definitive evidence. This study conducted a network meta-analysis (NMA) to evaluate the efficacy and safety of traditional Chinese medicine injections in the treatment of DKD to provide a reference for clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…There are many meta-analysis studies of other TCM dosage forms for treating diabetic nephropathy. For example, Long C’s network meta-analysis ( Long et al, 2023 ) reported that the total effective rate of combined Salvia miltiorrhiza injection, Danshen-Chuanxiongqin injection, Danhong injection, Huangqi injection, and Shenkang injection combined with alprostadil injection (PGE1) was better than PGE1 alone. Within all subgroups, they found that PGE1+Shenkang injection was most effective for glomerular filtration function, while PGE1+Danhong injection was most effective for urinary protein-related indices.…”
Section: Discussionmentioning
confidence: 99%
“…There are many meta-analysis studies of other TCM dosage forms for treating diabetic nephropathy. For example, Long C’s network meta-analysis ( Long et al, 2023 ) reported that the total effective rate of combined Salvia miltiorrhiza injection, Danshen-Chuanxiongqin injection, Danhong injection, Huangqi injection, and Shenkang injection combined with alprostadil injection (PGE1) was better than PGE1 alone. Within all subgroups, they found that PGE1+Shenkang injection was most effective for glomerular filtration function, while PGE1+Danhong injection was most effective for urinary protein-related indices.…”
Section: Discussionmentioning
confidence: 99%